Implementasi Strategi Coping Stress dalam Upaya Mengatasi Perilaku Bullying di Pondok Pesantren Al-Hikmah Gedanganak Ungaran - Priarni, Rina; Rosidi, Ayep; Listya, Serani Dara (Cakrawala : Jurnal Kajian Manajemen Pendidikan Islam dan Studi Sosial, 2024)
This research aims to describe in detail how to implement stress coping strategies in an effort to overcome bullying behavior at the Al-Hikmah Gedang Islamic boarding school for children in Ungaran. This research uses a qualitative approach. Data collection was carried out through observation, in-depth interviews and documentation. Data analysis is carried out by giving meaning to the data that has been collected and from that meaning conclusions are drawn. The results of the research show that the implementation of stress coping strategies at the Al-Hikmah Gedanganak Islamic boarding school uses Emotional focused coping, including self-control, seeking social support, positive reinterpretation, acceptance and denial. Implementation activities for stress coping strategies begin with planning, implementation and evaluation using the CIPP evaluation model, namely Context, Input, Process, Product. Keywords: Bullying, coping stress, Islamic boarding school